An Empirical Analysis on Cultivation Behaviour of Bt Cotton Growers - S. Usha Rani; G. Selvaraj (Journal of Agricultural Extension Management, 2025)
The decision of the Genetic Engineering Approval Committee (GEAC) of the Government of India ( GOI) clearing the release of the nation’s first Genetically Engineered (GE) crop "Bt cotton" for commercial cultivation during 2002-03 crop seasons is considered one of the major milestones in the history of cotton improvement in India. Incidentally, cotton happens to be the first crop to receive environment clearance as Genetically Modified Organisms (GMOs) in Indian agriculture. It has received maximum attention from planners, scientists, social workers, media, farmers and the general public both in India and outside, as it is a landmark decision paving way for more crops in India